Examining antecedents and outcomes to develop a holistic understanding of loneliness in work - Frost, Fiona Jane Marie (2024)
The overarching research purpose is to develop a more robust and comprehensive understanding of loneliness in work using a mixed methods research design. This research is timely and of great importance; the challenges of loneliness in work are increasingly salient due to global technological advancements and digitalisation, and their major impact on how work is designed, managed, and organised (EC, 2022; EESC, 2017; ILO, 2022; OECD, 2019). These pre-existing long-term dynamics towards the expansion of alternative forms of work, including remote work and hybrid work, have been further exacerbated by the Covid-19 pandemic (Cigna, 2020; OECD 2021; Makey et al., 2024; Niebuhr et al., 2022). Overall, notions of flexibility have been recast, with 65 percent of the global workforce expected to consist of entirely remote workers in five years (Ozimek, 2020). The increased prevalence of loneliness in work is a direct consequence of this significant increase in remote working (Groarke et al., 2020).